Labrune Syndrome: A Very Rare Association of Leukoencephalopathy, Cerebral Calcifications, and Cysts - Joshi, Anagha R.; Kulkarni, Kiran; Shah, Ankita U. (Indian Journal of Radiology and Imaging, 2021)
Leukoencephalopathy, cerebral calcifications, and cysts (LCC) form a very rare association which is named as “Labrune syndrome” after Labrune who reported the first case in 1996. To the best of our knowledge only eight to 10 cases have been reported in literature to date. We report a case of a 26-year-old male with onset of neurological symptoms in late adolescence (at 19 years of age) and presented with complains of continued seizures for 7 years, giddiness with imbalance, and slowly progressive motor symptoms. MRI brain revealed multiple calcifications in bilateral basal ganglia, cerebral white matter, multiple cystic lesions in the supratentorial white matter, and abnormal diffused bilateral white matter T2 hyperintensity suggesting leukoencephalopathy. Histopathological evaluation revealed prominent congested blood vessels suggestive of angiomatous changes and cystic areas suggestive of secondary gliosis.
Keywords: Labrune syndrome; leukoencephalopathy; cerebral calcifications; cysts